2013
DOI: 10.1016/j.matbio.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Decorin expression is important for age-related changes in tendon structure and mechanical properties

Abstract: The aging population is at an increased risk of tendon injury and tendinopathy. Elucidating the molecular basis of tendon aging is crucial to understanding the age-related changes in structure and function in this vulnerable tissue. In this study, the structural and functional features of tendon aging are investigated. In addition, the roles of decorin and biglycan in the aging process were analyzed using transgenic mice at both mature and aged time points. Our hypothesis is that the increase in tendon injurie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
233
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(254 citation statements)
references
References 40 publications
18
233
3
Order By: Relevance
“…This fibrillar organization is essential for tendons to bear the stress of muscle contraction and prevent bone detachment (avulsion fractures) by controlling force distribution Pan et al, 2013;Schwartz et al, 2013;Pingel et al, 2014). The fibrillar network of proteins includes: (1) Dunkman et al, 2013). Although the integration of structural collagens into fibrils has been well documented, recent studies have provided insight into the functions of scaffolding proteins and specialized collagens during fibril assembly.…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 99%
See 1 more Smart Citation
“…This fibrillar organization is essential for tendons to bear the stress of muscle contraction and prevent bone detachment (avulsion fractures) by controlling force distribution Pan et al, 2013;Schwartz et al, 2013;Pingel et al, 2014). The fibrillar network of proteins includes: (1) Dunkman et al, 2013). Although the integration of structural collagens into fibrils has been well documented, recent studies have provided insight into the functions of scaffolding proteins and specialized collagens during fibril assembly.…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 99%
“…These are found in relatively small amounts in tendons, yet loss-of-function mutations in the genes encoding these proteins disrupt collagen fibrillogenesis (Chakravarti, 2002;Corsi et al, 2002;Zhang et al, 2006). SLRPs mainly crosslink collagen fibrils, but they also appear to cross-regulate one another's transcription through as yet unknown mechanisms (Yoon and Halper, 2005;Zhang et al, 2006;Dunkman et al, 2013). This might involve feedback regulation of Scx and Mkx expression through the tendon ECM, and recent studies have suggested that Dcn and Fmod are regulated by Mkx (Fig.…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 99%
“…Twenty specimens from each group designated for dynamic viscoelastic testing were subjected to a testing protocol as described previously [13,14,40]. Tendons were first preloaded and preconditioned for 10 cycles to 1.5% grip strain at 0.25 Hz.…”
Section: Dynamic Viscoelastic Testingmentioning
confidence: 99%
“…In addition, the dynamic modulus jE*j (defined as the stress amplitude divided by the strain amplitude) and the phase angle d (between the stress and strain) were computed at each frequency and strain level. The dynamic modulus (jE*j) represents how difficult the material is to deform under dynamic loading, while the tangent of the phase angle (tan d) is the ratio of loss over storage moduli [13,14,40,42]. Comparisons were made using one-way ANOVA for each parameter with post-hoc Bonferroni tests to correct for family-wise error associated with multiple comparisons.…”
mentioning
confidence: 99%
“…The major proteoglycan present in the proximal/tensional regions of the tendon is decorin [16][17][18], even though lower amounts of other proteoglycans, such as biglycan, aggrecan and versican, have also been detected [19,20]. Decorin and biglycan belong to the small leucine-rich family of proteoglycans (characterized by leucine-rich repeat structures) which have been proposed to be directly involved in the binding of proteoglycans to collagen [21].…”
Section: Tendons Biochemical Composition and Ultrastructurementioning
confidence: 99%